PROBLEMATIKA YURIDIS PENGEMBALIAN STATUS APARATUR SIPIL NEGARA PADA KEMENTERIAN KOPERASI DAN UKM: Juridical Problem Regarding the Reinstatement of the Status of Civil Servants at the Ministry of Cooperatives and SMEs - Izeth Belthazar Hamonangan; Rido, Ali (Reformasi Hukum Trisakti, 2024)
This research addresses the case of a Civil Servant who was previously dismissed honorably not at their own request but later had their civil servant status restored based on Decision Number 17/G/2023/PT.TUN.JKT. The research problem focuses on whether the reinstatement of the civil servant's status aligns with legal regulations and what the legal consequences of this reinstatement are. The study employs a normative legal research method with a descriptive nature. It uses secondary data, analyzed through qualitative methods, and draws conclusions using deductive reasoning. The findings and results is indicate that the reinstatement of the civil servant's status does not comply with legal regulations, as it does not involve the imposition of disciplinary penalties twice. The legal consequence is the emergence of an obligation for the Civil Service Consideration Board to issue a Decree concerning the revocation of the decision of Honorable Dismissal Not at One’s Own Request for ZPA, and ZPA's reinstatement as a Civil Servant.